Response to therapy with direct antiviral drugs in HCV-infected patients with diabetes - Michał Brzdęk; Dorota Zarębska-Michaluk; Piotr Rzymski; Beata Lorenc; Justyna Janocha-Litwin; Hanna Berak; Krzysztof Tomasiewicz; Marek Sitko; Włodzimierz Mazur; Ewa Janczewska; Dorota Dybowska; Jakub Klapaczyński; et al. (Scientific Reports)
Abstract The clinical and metabolic interactions between hepatitis C virus (HCV) infection and diabetes mellitus (DM) are well documented. The study aimed to compare HCV-infected patients with and without DM. The analysis included 18,968 patients treated with direct-acting antivirals (DAAs) between 2015 and 2023, whose data were collected retrospectively. In the study population, 2179 patients (11.5%) were diagnosed with DM. Compared to the non-diabetic population, they were male-dominated (p = 0.003), had a significantly higher proportion of patients aged ≥ 50 years (p < 0.001), and were more burdened with comorbidities (p < 0.001). The most common HCV genotype was 1b with a significantly higher prevalence in the diabetic group (p < 0.001). Liver disease advancement was higher in diabetic patients, with 17.9% advanced fibrosis and 48% cirrhosis compared to 13.2% (p < 0.001) and 21.8% (p < 0.001) in the non-diabetic population. The effectiveness of DAA therapy in patients with DM was significantly lower compared to the population without diabetes, both in intent-to-treat analysis 93.1% vs. 94.6%, p = 0.015, and per-protocol analysis 96.8% vs. 97.7%, p = 0.0128, however, logistic regression analysis did not confirm the role of diabetes as an independent predictor of treatment failure, suggesting that in the absence of other negative prognostic factors, DM alone does not reduce the chances of cure.